Cover Feature: Co‐Polymeric Nanosponges from Cellulose Biomass as Heterogeneous Catalysts for amine‐catalyzed Organic Reactions (ChemCatChem 24/2020). Issue 24 (19th November 2020) - Riva, Laura; Punta, Carlo; Sacchetti, Alessandro
Abstract : The Cover Feature shows a highly porous cellulose‐based nanosponge (CNS) used as a recoverable catalyst for Henry and Knoevenagel reactions. This material is obtained by cross‐linking TEMPO‐oxidized cellulose nanofibers (TOCNF) and branched polyethyleneimine 25 kDa (bPEI) in the presence of citric acid. In their Full Paper, L. Riva et al. describe a micro‐ and nano‐porous system that ensures a complete penetration of the reagents within the CNS, guaranteeing high conversions and remarkable selectivity by modulating the reaction conditions. The catalyst could be also re‐used several times without losing its catalytic efficiency. More information can be found in the Full Paper by L. Riva et al.